Maximum Peak-Gain Margin 2DOF-IMC Tuning for a 2DOF-PID Filter Set Point Controller Under Parametric Uncertainty - Nur Hidayah; Juwari Juwari; Renanto Handogo (Institut Teknologi Sepuluh Nopember, 2014)
The specification of controller setting for a standard controller typically requires a trade-off between set point tracking and disturbance rejection. For this reason two simple strategies can be used to adjust the set point and disturbance responses independently. These strategies are referred to as controllers with two degree of freedom. Unfortunately, the tuning parameters in the case of model uncertainty at two degree of freedom structure controller is difficult to obtain. Juwari et al (2013) has introduced maximum peak-gain margin (Mp-GM) tuning method to obtain setting parameter of two degree of freedom structure controller based on model uncertainty. This tuning method are able to obtain the good controller parameter even under processes uncertainties on standard two degree of freedom (was abbreviated as 2DOF) IMC. This research will be conducted on development maximum peak-gain margin tuning method for a two degree of freedom PID filter set point structure controller. The simulation results show that the maximum peak gain margin tuning method can give a good target set point tracking, disturbance rejection and robustness in system a 2DOF-PID filter set point controller.